Positive electrode material and lithium ion battery
By defining the crystal crystal coefficient P of the primary particles in the single crystal positive electrode material, increasing the number and gap of the crystal crystals, the problem of lengthening of the lithium ion transmission path is solved, and the capacity and rate performance of the lithium ion battery are improved.
Patent Information
- Application Number
- CN202411975725.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Single-crystal positive electrode material has the problem of the lengthening of the lithium ion transmission path in lithium-ion batteries, resulting in a decrease in capacity and poor rate performance.
By limiting the crystallite coefficient P of the primary particle to the range of 20000≤P≤100000, the number of crystallites and microcrystal gaps in the primary particle are increased, more lithium ion transmission channels are provided, DC internal resistance is reduced, and capacity is improved.
The discharge specific capacity and rate performance of lithium-ion batteries are improved, and the structural stability and cyclic stability of the positive electrode material are enhanced.
Smart Images

Figure CN119400854A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of positive electrode materials; more specifically, the present application relates to a positive electrode material and a lithium-ion battery. Background Art
[0002] In recent years, the large-scale deployment of electric vehicles and power storage systems has led to a sharp increase in global demand for lithium-ion batteries, precisely because lithium-ion batteries have high energy density and power density. In the prior art, compared with polycrystalline materials, single-crystal materials have longer lithium-ion transmission paths, and their discharge specific capacity and rate performance are worse than those of polycrystalline materials. Specifically, the main problem in single-crystal positive electrode materials is the size problem. Large primary particle size will cause the lithium-ion transmission path to become longer, the impedance to become larger, and the capacity to decrease; small primary particle size and insufficient growth will cause the primary particles to adhere to each other and cannot be separated to become polycrystalline-like. The strength of polycrystalline-like materials is low, and polycrystalline-like materials may gradually crack with the cycle, and the generation of new surfaces will cause side reactions in the material, thereby affecting the long-term performance of lithium-ion batteries. Summary of the invention
[0003] In order to at least solve one or more of the technical problems mentioned above, the present application proposes solutions for improving the prior art in multiple aspects.
[0004] In a first aspect, the present application provides a positive electrode material, the positive electrode material is a lithium nickel cobalt composite oxide, the positive electrode material comprises a plurality of crystal grains, and the crystal grains comprise primary particles; The positive electrode material has a primary particle crystallite coefficient P, , the crystallite coefficient P satisfies 20000≤P≤100000; Among them, d 104 is the interplanar spacing of the 104 crystal planes; and D is the length of the average longest axis of the primary particles.
[0005] In a second aspect, the present application provides a lithium-ion battery comprising the positive electrode material described in the first aspect.
[0006] The lithium-ion battery provided in the second aspect of the present application has the advantages of high discharge specific capacity, good rate performance and high ionic conductivity.
[0007] The present application provides a positive electrode material, which limits the crystallite coefficient P value of the primary particles to the range of 20000≤P≤100000, so that there are more crystallites in the primary particles, and a certain gap between the crystallites can provide a transmission channel for lithium ions, thereby increasing the lithium ion transmission channel in the primary particles, thereby reducing DCR (Direct Current Resistance) and improving the capacity of the battery. In addition, by increasing the number of crystallites in the primary particles, the problem of insufficient primary particle growth of traditional single crystal particles is solved; while the material grows into a large-particle single crystal, the number of crystallites in the particles is increased to enhance the ionic conductivity of the material, which not only solves the problem of large-particle single crystal growth, but also solves the problem of large-particle single crystal impedance and low capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] By reading the detailed description below with reference to the accompanying drawings, the above and other purposes, features and advantages of the exemplary embodiments of the present application will become easy to understand. In the accompanying drawings, several embodiments of the present application are shown in an exemplary and non-limiting manner, and the same or corresponding reference numerals represent the same or corresponding parts, wherein: Figure 1 Shown is a scanning electron microscope photograph of Example 1; Figure 2 Shown is a scanning electron microscope photograph of Example 2; Figure 3 Shown is a scanning electron microscope photograph of Example 3; Figure 4 Shown is a scanning electron microscope photograph of Example 4; Figure 5 A schematic diagram of a battery in a discharge state, i.e., during operation, is shown; Figure 6 A scanning electron microscope photograph of Comparative Example 1 is shown. DETAILED DESCRIPTION
[0009] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0010] It should be understood that the terms "include" and "comprising" used in the specification and claims of the present application indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0011] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. As used in this application specification and claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms. It should also be further understood that the term "and / or" used in this application specification and claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.
[0012] As used in this specification and claims, the term "if" can be interpreted as "when" or "upon" or "in response to determining" or "in response to detecting," depending on the context. Similarly, the phrases "if it is determined" or "if [described condition or event] is detected" can be interpreted as meaning "upon determination" or "in response to determining" or "upon detection of [described condition or event]" or "in response to detecting [described condition or event]," depending on the context.
[0013] The specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the examples of the present application are all obtained from conventional commercial channels.
[0014] In view of the shortcomings of the prior art, the purpose of the present application is to provide a positive electrode material, wherein the positive electrode material is a lithium nickel cobalt composite oxide, the positive electrode material comprises a plurality of crystal grains, the crystal grains comprise primary particles, wherein: The positive electrode material has a primary particle crystallite coefficient P, , the crystallite coefficient P satisfies 20000≤P≤100000; wherein, d 104 is the interplanar spacing of the 104 crystal plane; D is the length of the average longest axis of the primary particles.
[0015] It should be noted that a primary particle includes a plurality of crystallites. In the primary particle crystallite coefficient, D refers to the length of the average longest axis of the primary particle, D 3 is the size of the primary particles, d 104 is the size of the crystallite. It can be used to characterize the number of microcrystals in a primary particle. The average longest axis length of a primary particle can be measured by a SEM scanning electron microscope to obtain the longest axis of the primary particle; 104 The half-peak width of the 104 crystal plane can be obtained by XRD analysis, and then the half-peak width of the 104 crystal plane can be converted into the atomic parallel spacing by the Scherrer formula to obtain d 104 . Specifically, , d104 is the atomic parallel spacing of the 104 crystal plane (i.e., crystallite size); k is a constant; λ is the X-ray wavelength; β is the half-maximum width (FWHM) of the diffraction peak; θ is the diffraction angle.
[0016] Therefore, by limiting the P value to the range of 20000≤P≤100000, a certain number of crystallites can exist in the primary particles, and a certain gap between the crystallites can provide a transmission channel for lithium ions, thereby increasing the lithium ion transmission channel in the primary particles, thereby reducing DCR (Direct Current Resistance) and increasing the capacity of the positive electrode material. <20000, the number of microcrystals in the primary particles is insufficient, resulting in insufficient lithium ion transmission channels, and the effect of reducing DC internal resistance and increasing capacity cannot be achieved; when P> When it is 100000, the number of crystallites in the primary particles is too large, which may lead to a decrease in the structural strength of the primary particles, thereby affecting the cycle stability of the positive electrode material.
[0017] As an embodiment of the present invention, the positive electrode material meets the following conditions: In the XRD spectrum of the positive electrode material, there is a first peak between 2θ of 17°-20°, the first peak is 003 peak, and the half-peak width of the first peak is 0.08-0.20; the half-peak width of the first peak can be 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.18, 0.20 or any value within the range formed by any two of the above values, without limitation herein. There is a second peak between 2θ of 42°-45°, the second peak is 104 peak, and the half-peak width of the second peak is 0.10-0.30; the half-peak width of the second peak can be 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.22, 0.24, 0.26, 0.28 or any value within the range formed by any two of the above values, which is not limited here. Therefore, by limiting the half-peak widths of the first peak and the second peak within the above range, the grains of the positive electrode material have better microscopic strain while meeting the larger grain size, thereby increasing the structural stability of the grains and improving the cycle stability of the positive electrode material.
[0018] As an embodiment of the present invention, the positive electrode material has a 003 crystal plane interplanar spacing d 003 and the interplanar spacing d of the 104 crystal plane 104 .
[0019] Among them, d 003 The value range is 80-160nm, and the d 003It can be 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160 or any value within the range formed by any two of the above values, and is not limited here. 003 When it is within the above range, it indicates that the interplanar spacing on the 003 crystal plane is long enough, and the material forms a good layered structure at the microscopic level, thereby facilitating the deintercalation of Li ions, reducing DCR (Direct Current Resistance), and increasing the capacity of the positive electrode material.
[0020] Among them, d 104 The value range of d is 20-100nm; 104 It can be 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or any value within the range formed by any two of the above values, and is not limited here. 104 The value of meets the requirement of 20-100nm, so that the crystallite size within the primary particle can provide a certain structural strength, thereby improving the cycle stability of the positive electrode material.
[0021] As an embodiment of the present invention, the primary particles of the positive electrode material have an average longest axis length D, wherein D>2.0μm; the D can be 2.05μm, 2.10μm, 2.15μm, 2.20μm, 2.25μm, 2.30μm, 2.35μm, 2.40μm, 2.45μm, 2.50μm, 2.55μm, 2.60μm, 2.70μm, 2.80μm or any value within the range formed by any two of the above values, without limitation herein.
[0022] The average longest axis D is the average of the longest diameters of the primary particles in the SEM of the positive electrode material at multiples of 3K. Primary particles having a longer average longest axis within the above range indicate that the primary particles grow larger and more uniformly, and the primary particles have good structural strength.
[0023] As an embodiment of the present invention, the positive electrode material contains single grains with the same orientation, wherein the length of the longest axis of the single grain is 1µm~5µm. Specifically, the length of the longest axis of a single grain is 1µm, 2µm, 3µm, 4µm, 5µm or any value within the range formed by any two of the above values, which is not limited here. The orientation of the primary particles of the positive electrode material is the same, and the length of the longest axis of the primary particles is 1μm-5μm. Specifically, the length of the longest axis of the primary particles is 1µm, 2µm, 3µm, 4µm, 5µm or any value within the range formed by any two of the above values, which is not limited here. The positive electrode material particles of the present application have single grains with the same orientation. Since single crystals have a more stable structure, more uniform distribution of bulk components, and better particle strength than polycrystalline, the material can greatly reduce the cracking of particles during the pressing process of the pole piece, thereby improving the compaction density and volume energy density of the pole piece.
[0024] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to EBSD testing methods, characterization methods such as scanning electron microscopy (SEM) can also be used to determine whether the obtained positive electrode product is a single crystal material. For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and orientation. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0025] As an embodiment of the present invention, the chemical formula of the positive electrode material matrix is Li a Ni x M y N z X 1-x-y-z O 2b, wherein 0.98≤a≤1.05, 0.60≤x<1, 0<y≤0.40, 0<z≤0.003, 0.95≤b≤1.05, M is selected from at least one of Co, Mn, and Al, N is selected from at least one of Ti, Zr, Mg, Sr, Ba, Nb, W, and Y, and X is selected from one or more of W, Y, Mn, Os, Sb, V, and Cr. Preferably, 1.00≤a≤1.03, 0.60≤x<0.9, 0.1<y≤0.40, 0<z≤0.002, and 1.00≤b≤1.03.
[0026] In the above chemical formula, a may be 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05 or any value within the range formed by any two of the above values, and is not limited herein.
[0027] In the above chemical formula, b may be 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05 or any value within the range formed by any two of the above values, and is not limited herein.
[0028] In the above chemical formula, x may be 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95 or any value within the range formed by any two of the above values, and is not limited herein.
[0029] In the above chemical formula, y may be 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40 or any value within the range formed by any two of the above values, and is not limited herein.
[0030] In the above chemical formula, z may be 0.0005, 0.001, 0.0015, 0.0020, 0.0025, 0.0030 or any value within the range formed by any two of the above values, and is not limited herein.
[0031] In the above chemical formula, element X is a high-valent element with a valence greater than or equal to 5. Element X is selected from one or more of W, Y, Mn, Os, Sb, and V. The positive electrode material includes a plurality of grains, and the grains include an internal region. The distance between any point in the internal region and the surface of the grain is greater than 500nm, and at least part of the element X is located in the internal region of the grain. The element X is located in the internal region of the grain, and the cross-section of the grain can be characterized by ESD, showing that the element X is located in the internal region. Therefore, by containing a high-valent element X with a valence greater than or equal to 5 in the internal region of the grain, the high-valent element X can change the energy band structure of the grain, reduce the migration activation energy of electrons, thereby reducing the energy barrier for Li ion migration, and further reduce the DCR (Direct Current Resistance), thereby increasing the capacity of the positive electrode material.
[0032] As an embodiment of the present invention, the powder resistivity of the positive electrode material ; The powder resistivity can be, , , , , , , , Or any value within the range of any two of the above values, which is not limited here. Preferably, the powder resistivity ; More preferably, the powder resistivity By controlling the powder resistivity of the positive electrode material within the above range, the positive electrode material has excellent powder conductivity and low resistance, thereby reducing DCR (Direct Current Resistance) and increasing the capacity of the positive electrode material.
[0033] As an embodiment of the present invention, the tap density of the positive electrode material is ≥ 3.00 g / cc; the tap density can be 3.00 g / cc, 3.05 g / cc, 3.10 g / cc, 3.15 g / cc, 3.20 g / cc, 3.25 g / cc, 3.30 g / cc, 3.35 g / cc, 3.40 g / cc, 3.45 g / cc, 3.50 g / cc, 3.55 g / cc, 3.60 g / cc, 3.65 g / cc or any value within the range formed by any two of the above values, which is not limited herein. The tap density of the positive electrode material is one of the indicators for measuring the energy density of the material. If the tap density of the positive electrode material is too large, the positive electrode sheet is too dense, which is not conducive to the infiltration of the electrolyte into the positive electrode sheet, resulting in hindered lithium ion insertion and a decrease in the rate performance of the battery. If the tap density of the positive electrode material is too low, the energy density of the material will decrease. Controlling the tap density of the positive electrode material within the above range is beneficial for the positive electrode material to have both high energy density and excellent rate performance.
[0034] As an embodiment of the present invention, the median particle size D50 of the volume distribution particle size of the positive electrode material satisfies: 3 μm < D50 < 5 μm, and the volume distribution particle size D50 can be: 3.1 µm, 3.3 µm, 3.4 µm, 3.6 µm, 3.8 µm, 4 µm, 4.2 µm, 4.5 µm, 4.8 µm, 4.9 µm. Preferably, the median particle size D50 of the volume distribution particle size of the positive electrode material satisfies: 3.5 μm < D50 < 4.5 μm. The median particle size D50 represents the particle size of the material corresponding to when the cumulative particle size distribution percentage reaches 50% volume ratio. When the D50 of the positive electrode material is small, the particle size is small, the tap density is low, and the specific surface area is large, which easily leads to serious side reactions between the particle surface and the electrolyte, reducing safety and cycle life; when the D50 of the positive electrode material is large, the particle size is large, the internal stress of the particles increases, and at the same time, the electrochemical polarization and concentration polarization of lithium ions inside and outside the particles are aggravated, resulting in a decrease in the capacity and rate performance of the positive electrode material. Controlling the D50 of the positive electrode material within the above range is beneficial for the positive electrode material to maintain better tap density, specific capacity and cycle life.
[0035] As an embodiment of the present invention, the width of the volume particle size distribution of the positive electrode material satisfies: 1.0 ≤ Span ≤ 1.8; wherein, .
[0036] The characteristic particle size distribution width is represented by the function ; the above formula represents a typical particle size distribution width function.
[0037] The value of the volume particle size distribution width of the positive electrode material can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.8. The larger the span value, the wider the material particle size distribution. A wider particle size distribution is beneficial to improving the space utilization when the material is stacked. Small particles fill the gaps between large particles, and smaller particles fill in smaller gaps. High space utilization requires a sufficient combination of small and large particles, which requires a wider particle size distribution. Therefore, as mentioned above, the span value represents the width of the particle size distribution. By controlling the span value of the positive electrode material to be within the above range, it is beneficial to improve the powder compaction density of the material and reduce the powder resistance.
[0038] As an embodiment of the present invention, the ratio of the discharge capacity to the charge capacity of the positive electrode material at 0.1C is ≥90.0%, and the ratio of the discharge capacity to the discharge capacity at 0.5C of the positive electrode material is ≥96.5%. The ratio of the discharge capacity to the charge capacity of the positive electrode material at 0.1C may be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%. The ratio of the discharge capacity to the discharge capacity at 0.1C of the positive electrode material may be 96.5%, 96.6%, 96.7%, 96.8%, 96.9%, 97%, 97.4% or 97.5%. Controlling the specific capacity within the above range is beneficial to maintaining a better energy density and cycle life of the positive electrode material.
[0039] The present application also relates to a method for preparing a high-capacity positive electrode material, the preparation method comprising the following steps: Step S1, preparing a solution of metal salts of Ni, Co and Mn in a certain ratio; adjusting the concentration of the solution; spraying the solution into a pyrolysis tower for reaction, and finally obtaining an oxide precursor.
[0040] Among them, the precursor is prepared by the above-mentioned preparation method, and the reaction time is short, the pollution is less, and the cost is low. And the precursor prepared by the above-mentioned method, at least part of the precursor has a spinel structure, and the precursor of the spinel structure is more likely to form a layered structure when forming a positive electrode material. Specifically, the precursor obtained by the above-mentioned preparation method belongs to a two-phase mixture of spinel and rock salt phase, which is closer to the layered phase than the structure of the co-precipitated precursor. Therefore, in the reaction phase change process, even if there is interference from high-valent transition metal elements, it is easier to grow into a good layered structure, thereby providing better conditions for subsequent high-valent element doping. On the other hand, compared with the co-precipitation process commonly used in the prior art, the precursor material obtained by co-precipitation has low crystallinity and poor tolerance to large-radius element doping. High-valent elements are easy to adhere to the surface of the material and then inhibit crystal growth into dispersion, making it difficult to form good single crystal particles. Moreover, the precursor prepared by the above preparation method is an oxide, and the oxide is formed in an environment with a temperature of more than 600°C, with a high degree of oxidation, and part of the lattice in the precursor forms a spinel phase with a higher lattice order. The chemical reaction energy required to transform from an ordered spinel phase or a rock salt phase into a layered phase is lower, and it is easier to form an ordered layered phase, which is beneficial to reduce the half-peak width of the 104 peak of the positive electrode material.
[0041] In some embodiments, metal salts of Ni, Co, and Mn are prepared into a solution in a certain ratio. For example, the solution may be at least one of a nitrate solution, a sulfate solution, a chloride solution, and an acetate solution; in the metal salt solution of Ni, Co, and Mn, the molar ratio of Ni, Co, and Mn may be 3-9:1-4:1-4, and the sum of the molar ratios of Ni, Co, and Mn is 1. For example, the above molar ratio may be any value of 6:1:3, 8:1:1, or 5:2:3.
[0042] In some embodiments, the precursor obtained in step S1 is an oxide; the general formula of the precursor is Ni x M y N 1-x-y O b , wherein 0.60≤x<1, 0<y≤0.40, 0.95≤b≤1.05. Preferably, 0.60≤x<0.9, 0<y≤0.30, 0.98≤b≤1.05.
[0043] In some embodiments, the concentration of the solution ranges from 0.05 mol / L to 2 mol / L. For example, the concentration of the solution can be 0.05 mol / L, 0.07 mol / L, 0.08 mol / L, 0.14 mol / L, 0.36 mol / L, 0.66 mol / L, 0.89 mol / L, 1.13 mol / L, 1.45 mol / L, 1.68 mol / L, 2 mol / L, or any value within the range formed by any two of the above values.
[0044] In some embodiments, the solution is sprayed into a pyrolysis tower, wherein the nozzle pressure is 1-5 MPa. The nozzle pressure can be 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa, 5 MPa, or any value within the range of any two of the above values, without limitation. Preferably, the nozzle pressure is 3.3-5 MPa.
[0045] The temperature in the pyrolysis tower is 600-1050° C. The temperature can be 600° C., 650° C., 700° C., 750° C., 800° C., 850° C., 900° C., 950° C., 1000° C., 1050° C. or any value within the range formed by any two of the above values, which is not limited here.
[0046] Step S2, mixing the precursor, lithium source and dopant obtained by spray pyrolysis and performing a first heat treatment to obtain a pre-burned product; then adding the lithium source and mixing with the pre-burned product and performing a second heat treatment to obtain a sintered product.
[0047] Among them, by controlling the lithium content during the first heat treatment process, reducing the position occupied by Li ions in the bulk phase, it is convenient for the high-valent element X to enter the bulk phase, thereby improving the doping effect of the high-valent element X; and, during the first heat treatment process, the heat treatment temperature is low, which can promote the doping of the high-valent element X into the bulk phase. After the high-valent element X enters the bulk phase, it can increase the nucleation energy barrier and reduce the crystal nucleus density. The lower crystal nucleus density means that there are more raw materials around each crystal nucleus for growth, which is beneficial to the growth of primary particles. The temperature of the first heat treatment is low, which promotes the growth of microcrystals in the primary particles, increases the half-peak width of the 104 crystal plane, reduces the interplanar spacing of the 104 crystal plane, and makes the number of microcrystals within a suitable range. By continuing to increase the lithium source during the second heat treatment process, the temperature of the second heat treatment is high, which promotes the growth of the primary particles and controls the length of the major axis of the primary particles to be within a suitable range.
[0048] In some embodiments, the dopant further comprises an element X, the valence state of the element X is ≥5, and the element X is selected from one or more of W, Y, Mn, Os, Sb, and V. Thus, by having a valence state of the element X in the dopant greater than 5, the high-valence doping element X can promote the growth of primary particles to control the length of the average longest axis of the primary particles.
[0049] In some embodiments, the dopant containing element X may be an oxide, a hydroxide, or an oxyhydroxide. For example, the dopant containing element X may be WO3, Y2O5, OsO4, V2O5, Sb2O5, CrO3, or Mn2O7.
[0050] In some embodiments, the dopant may further include an oxide, a hydroxide, or an oxyhydroxide of element N; element N is selected from at least one of Ti, Zr, Mg, Sr, Ba, Nb, W, and Y.
[0051] In some embodiments, the lithium source may be in the form of lithium carbonate, lithium hydroxide, lithium nitrate or lithium chloride.
[0052] In some embodiments, the molar ratio of the precursor to the total amount of the added lithium source may be 1:0.98-1.1. For example, the molar ratio of the precursor to the total amount of the added lithium source may be 1:0.98, 1:0.99, 1:1.02, 1:1.05, 1:1.10, or any value within the range of any two of the above values, which is not limited here.
[0053] In some embodiments, the lithium source added in the first heat treatment accounts for 30-90% of the total amount of the lithium source added. For example, the lithium source added before the first heat treatment accounts for 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90% of the total amount of the lithium source added, or any value within the range formed by any two of the above values, which is not limited here. Preferably, 40-80%, more preferably 50-65%. Thus, by controlling the addition of an appropriate amount of lithium source in the first heat treatment, the position occupied by Li ions in the bulk phase can be reduced, so that the high-valent element X enters the bulk phase, the doping effect of the high-valent element X is improved, the growth of the primary particles is facilitated, and the length of the longest axis of the primary particles is within a suitable range.
[0054] In some embodiments, the lithium source added in the second heat treatment accounts for 10-70% of the total amount of the lithium source added. For example, the lithium source added before the second heat treatment accounts for 10%, 20%, 30%, 40%, 45%, 50%, 60%, 70% or any value within the range formed by any two of the above values, preferably 20-60%, and more preferably 35-50%.
[0055] In some embodiments, the first heat treatment is preferably carried out in an air atmosphere, and the temperature range of the first heat treatment is 600°C to 1000°C. Controlling the temperature of the first heat treatment within the above range is conducive to the doping of high-valent element X into the bulk phase, and the growth of primary particles, promoting the physical and chemical nucleation of the positive electrode material in advance, so that the length of the longest day in the primary particles is within a suitable range. The temperature of the first heat treatment can be 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, any value within the range of any two of the above values, not limited here. The temperature of the first heat treatment is preferably 780°C to 980°C, more preferably 850°C to 950°C.
[0056] In some embodiments, the time of the first heat treatment is 1h-8h. Controlling the temperature of the first heat treatment to be within the above range is conducive to promoting the doping of the high-valent element X into the bulk phase, thereby facilitating the growth of the primary particles and controlling the longest axis of the primary particles to be within a suitable range. The time of the first heat treatment can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, any value within the range formed by any two of the above values, without limitation. Preferably, the time of the first heat treatment is 2h-6h, and more preferably, the time of the first heat treatment is 3.5h-4h.
[0057] In some embodiments, the second heat treatment is preferably carried out in an oxygen atmosphere, and the temperature range of the second heat treatment is 800°C to 1100°C. By controlling the temperature of the second heat treatment to be within the above range, the number of crystallites of the primary particles can be controlled, so that the length of the longest axis of the primary particles is within a suitable range. The temperature of the second heat treatment can be 800°C, 820°C, 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, 1020°C, 1050°C, 1080°C, 1100°C, any value within the range composed of any two of the above values, and is not limited here. Preferably, the temperature of the second heat treatment is 910°C to 1030°C, and more preferably, the temperature of the second heat treatment is 930°C to 970°C.
[0058] In some embodiments, the second heat treatment time is 6h-16h. The second heat treatment time can be 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, 12h, 13h, 14h, 15h, 16h, any value within the range of any two of the above values, not limited here. Preferably, the second heat treatment time is 7h-12h, more preferably, the second heat treatment time is 7.5h-8.5h.
[0059] Step S3, crushing the first sintered product, mixing it with the coating, and sintering it to obtain the positive electrode material.
[0060] In some embodiments, the coating contains at least one of the following elements: B, Ti, W, Al, Mg.
[0061] In some embodiments, the coating includes at least one of WO 3 , TiO 2 , and Al(OH) 3 . For example, the coating may be WO 3 , TiO 2 , Al(OH) 3 , a mixture of WO 3 and TiO 2 , or a mixture of WO 3 and Al(OH) 3 .
[0062] In some embodiments, based on the first sintered product, the mass fraction of the coating is 0.05-0.45wt.%. For example, the mass fraction of the coating is 0.05wt.%, 0.08wt.%, 0.10wt.%, 0.20wt.%, 0.25wt.%, 0.32wt.%, 0.40wt.%, 0.45wt.%. Preferably, based on the first sintered product, the mass fraction of the coating is 0.20-0.35wt.%.
[0063] In some embodiments, the temperature range of the secondary sintering is 400°C-550°C. The temperature of the secondary sintering can be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 550°C, and any value within the range formed by any two of the above values, and is not limited here. Preferably, the temperature range of the secondary sintering is 420°C-480°C.
[0064] An embodiment of the present application provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), comprising a housing, an electrode assembly, and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing.
[0065] The outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.
[0066] Figure 5 FIG. 1 shows a schematic diagram of a battery in a discharge state, that is, during operation. Figure 5 As shown, the electrode assembly includes a positive electrode sheet 110, a negative electrode sheet 120 and a separator 130, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.
[0067] Positive electrode The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode active layer contains a positive electrode active material, which includes a compound that reversibly embeds and de-embeds metal ions.
[0068] Negative plate The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The negative electrode active material layer includes a negative electrode material.
[0069] During battery operation, that is, when the battery is in a discharged state, the metal ions (such as lithium ions) in the negative electrode are released from the lattice of the negative electrode material, pass through the isolation membrane through the electrolyte / electrolyte, and are embedded in the lattice of the positive electrode material.
[0070] Conversely, when the battery is charged by applying an external circuit, the oxidation of the positive electrode material causes the metal ions (such as lithium ions) in the positive electrode to escape from the lattice of the positive electrode material, pass through the isolation membrane through the electrolyte / electrolyte, and move to the negative electrode; at the same time, the negative electrode material undergoes a reduction reaction, causing the metal ions to be embedded in the lattice of the negative electrode material.
[0071] As metal ions move back and forth between the positive and negative electrodes, the battery can be discharged and charged thousands of times.
[0072] Specific Examples and Comparative Examples Example 1 1. Ni, Co, and Mn nitrates are prepared into a nitrate solution in a molar ratio of 6:1:3; the concentration of the nitrate solution is adjusted to 0.1 mol / L; the nitrate solution is sprayed into a pyrolysis tower for reaction, the nozzle pressure is set to 3.3 MPa, and the temperature in the pyrolysis tower is set to 900°C to obtain an oxide precursor Ni0.6 Co 0.1 Mn 0.3 O.
[0073] 2. Mix the oxide precursor, lithium carbonate and WO3 and perform the first heat treatment. During the first heat treatment, the molar ratio of lithium carbonate to the precursor is 0.60:1, and the mass content of WO3 is 0.10wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, the treatment time is 4h, and the pre-sintered product is obtained after cooling. Continue to add lithium carbonate and mix with the pre-sintered product for the second heat treatment. During the second heat treatment, the molar ratio of lithium carbonate added to the precursor is 0.43:1, the sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0074] 3. The first sintered product is pulverized by jet milling and mixed with WO3 and TiO2 to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, and the mass content of TiO2 is 0.10wt.% of the first sintered product. The sintering temperature is 420℃. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0075] Example 2 1. Prepare a nitrate solution of Ni, Co and Mn in a molar ratio of 6:1:3; adjust the concentration of the solution to 0.15 mol / L; spray the solution into a pyrolysis tower for reaction, set the nozzle pressure to 5 MPa, and the temperature in the pyrolysis tower to 950°C to obtain an oxide precursor Ni 0.6 Co 0.1 Mn 0.3 O.
[0076] 2. The oxide precursor is mixed with lithium carbonate, WO3 and ZrO2 and then subjected to the first heat treatment, wherein the molar ratio of lithium carbonate added to the precursor in the first heat treatment is 0.6:1, the mass content of WO3 is 0.12wt.%, and the mass content of ZrO2 is 0.22wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, and the treatment time is 4h. After cooling, a pre-burned product is obtained, and lithium carbonate is continued to be added to mix with the pre-burned product for a second heat treatment, wherein the molar ratio of lithium carbonate added to the precursor in the second heat treatment is 0.43:1, the sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0077] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, the mass content of TiO2 is 0.05wt.% of the first sintered product, and the mass content of Al(OH)3 is 0.05 wt.% of the first sintered product. The sintering temperature is 440°C. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0078] Example 3 1. Prepare a sulfate solution of Ni, Co and Mn in a molar ratio of 6:1:3; adjust the concentration of the solution to 0.1 mol / L; spray the solution into a pyrolysis tower for reaction, set the nozzle pressure to 3.5 MPa, and the temperature in the pyrolysis tower to 950°C to obtain an oxide precursor Ni 0.6 Co 0.1 Mn 0.3 O.
[0079] 2. The obtained oxide precursor is mixed with lithium nitrate, WO3 and ZrO2 and then subjected to the first heat treatment. During the first heat treatment, the molar ratio of lithium nitrate to precursor is 0.6:1, the mass content of WO3 is 0.15wt.%, and the mass content of ZrO2 is 0.22wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, the treatment time is 4h, and the pre-sintered product is obtained after cooling. Lithium nitrate is added to the pre-sintered product for the second heat treatment. The molar ratio of lithium nitrate added to the precursor in the second heat treatment is 0.43:1. The sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0080] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, the mass content of TiO2 is 0.05wt.% of the first sintered product, and the mass content of Al(OH)3 is 0.05 wt.% of the first sintered product. The sintering temperature is 440°C. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0081] Example 4 1. Prepare a sulfate solution of Ni, Co and Mn in a molar ratio of 6:1:3; adjust the concentration of the sulfate solution to 0.1 mol / L; spray the sulfate solution into a pyrolysis tower for reaction, set the nozzle pressure to 5 MPa, and the temperature in the pyrolysis tower to 900°C to obtain an oxide precursor Ni 0.6 Co 0.1 Mn 0.3 O.
[0082] 2. Mix the oxide precursor with lithium nitrate, WO3 and ZrO2 and perform the first heat treatment. During the first heat treatment, the molar ratio of lithium nitrate to precursor is 0.6:1, the mass content of WO3 is 0.12wt.% of the mass of the precursor, and the mass content of ZrO2 is 0.22wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, the treatment time is 4h, and the pre-sintered product is obtained after cooling. Continue to add lithium nitrate and mix with the pre-sintered product for the second heat treatment. The molar ratio of lithium nitrate added to the precursor in the second heat treatment is 0.43:1, the sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0083] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.20wt.% of the first sintered product, the mass content of TiO2 is 0.15wt.% of the first sintered product, the mass content of Al(OH)3 is 0.05wt.% of the first sintered product, and the sintering temperature is 440℃. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0084] Example 5 1. Prepare a sulfate solution of Ni, Co and Mn in a molar ratio of 6:1:3; adjust the concentration of the sulfate solution to 0.1 mol / L; spray the solution into a pyrolysis tower for reaction, set the nozzle pressure to 3.5 MPa, and the temperature in the pyrolysis tower to 900°C to obtain an oxide precursor Ni 0.6 Co 0.1 Mn 0.3 O.
[0085] 2. The oxide precursor is mixed with lithium carbonate, V2O5 and ZrO2 and then subjected to the first heat treatment. During the first heat treatment, the molar ratio of lithium carbonate to the precursor is 0.6:1, the mass content of V2O5 is 0.12wt.% of the mass of the precursor, and the mass content of ZrO2 is 0.22wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, the treatment time is 4h, and the pre-sintered product is obtained after cooling. Lithium carbonate is added to the pre-sintered product and mixed for the second heat treatment. The molar ratio of lithium carbonate to the precursor in the second heat treatment is 0.43:1, the sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0086] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, the mass content of TiO2 is 0.05wt.% of the first sintered product, and the mass content of Al(OH)3 is 0.05 wt.% of the first sintered product. The sintering temperature is 440°C. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0087] Example 6 1. Prepare a nitrate solution with a molar ratio of 6:1:3 for Ni, Co and Mn nitrates; adjust the concentration of the solution to 0.15 mol / L; spray the solution into a pyrolysis tower for reaction; set the nozzle pressure to 5 MPa and the temperature in the pyrolysis tower to 900°C to obtain an oxide precursor Ni 0.6 Co 0.1 Mn 0.3 O.
[0088] 2. The oxide precursor is mixed with lithium carbonate, Nb2O5 and ZrO2 and then subjected to the first heat treatment, wherein the molar ratio of lithium carbonate added to the precursor in the first heat treatment is 0.6:1, the mass content of Nb2O5 is 0.12wt.% of the mass of the precursor, and the mass content of ZrO2 is 0.22wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, the treatment time is 4h, and the pre-sintered product is obtained after cooling. Lithium carbonate is added to the pre-sintered product for the second heat treatment, wherein the molar ratio of lithium carbonate added to the precursor in the second heat treatment is 0.43:1, the sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0089] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, the mass content of TiO2 is 0.05wt.% of the first sintered product, and the mass content of Al(OH)3 is 0.05 wt.% of the first sintered product. The sintering temperature is 440°C. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0090] Example 7 1. Prepare a nitrate solution with a molar ratio of 8:1:1 for Ni, Co and Mn nitrates; adjust the concentration of the solution to 0.1 mol / L; spray the solution into a pyrolysis tower for reaction, set the nozzle pressure to 3.5 MPa, and the temperature in the pyrolysis tower to 950°C to obtain an oxide precursor Ni 0.8 Co 0.1 Mn 0.1 O.
[0091] 2. The oxide precursor is mixed with lithium nitrate, OsO4 and Y2O5 and then subjected to the first heat treatment. During the first heat treatment, the molar ratio of lithium nitrate to precursor is 0.6:1, the mass content of OsO4 is 0.05wt.%, and the mass content of Y2O5 is 0.12wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C, the treatment time is 4h, and the pre-sintered product is obtained after cooling. Lithium nitrate is added to the pre-sintered product and mixed for the second heat treatment. The molar ratio of lithium nitrate added to the precursor in the second heat treatment is 0.43:1, the sintering temperature of the second heat treatment is 900°C, and the heat treatment time is 8h to obtain the first sintered product.
[0092] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, the mass content of TiO2 is 0.05wt.% of the first sintered product, and the mass content of Al(OH)3 is 0.15 wt.% of the first sintered product. The sintering temperature is 460°C. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0093] Example 8 1. Prepare a nitrate solution of Ni, Co and Mn in a molar ratio of 5:2:3; adjust the concentration of the solution to 0.1 mol / L; spray the solution into a pyrolysis tower for reaction, set the nozzle pressure to 3.3 MPa, and the temperature in the pyrolysis tower to 900°C to obtain an oxide precursor Ni 0.5 Co 0.2 Mn 0.3 O.
[0094] 2. The obtained oxide precursor is mixed with lithium carbonate, ZrO2 and Y2O5 and then subjected to the first heat treatment. During the first heat treatment, the molar ratio of lithium carbonate to the precursor is 0.6:1, the mass content of ZrO2 is 0.32wt.%, and the mass content of Y2O5 is 0.12wt.% of the mass of the precursor. The temperature of the first heat treatment is 780°C and the treatment time is 4h. After cooling, a pre-calcined product is obtained. Lithium carbonate is continued to be added to the pre-calcined product and mixed for the second heat treatment. In the second heat treatment, the molar ratio of lithium carbonate added to the precursor is 0.43:1. The sintering temperature of the second heat treatment is 910°C and the heat treatment time is 8h to obtain the first sintered product.
[0095] 3. The first sintered product is crushed and mixed with WO3, Al(OH)3 and TiO2 for sintering to obtain the positive electrode material. The mass content of WO3 is 0.15wt.% of the first sintered product, the mass content of TiO2 is 0.05wt.% of the first sintered product, and the mass content of Al(OH)3 is 0.15 wt.% of the first sintered product. The sintering temperature is 460°C. The chemical formula of the positive electrode material is: LiNi 0.6 Co 0.1 Mn 0.3 O2.
[0096] Example 9 The difference between this embodiment and embodiment 1 is that during the first heat treatment, the molar ratio of lithium carbonate to the precursor is 0.30:1, the mass content of WO3 is 0.25wt.% of the mass of the precursor, and the temperature of the first heat treatment is 700°C.
[0097] Example 10 The difference between this embodiment and embodiment 1 is that during the first heat treatment, the molar ratio of lithium carbonate to the precursor is 0.20:1, the mass content of WO3 is 0.30wt.% of the mass of the precursor, and the temperature of the first heat treatment is 600°C.
[0098] Comparative Example 1 1. Co-precipitate the precursor Ni 0.6 Co 0.1 Mn 0.3A mixture of (OH)2, lithium carbonate with a molar ratio of 1.03:1 to the precursor and 0.32wt.% ZrO2 as a dopant is sintered once at a temperature of 900°C to obtain a first sintered product; the weight percentage in step 1 is based on the weight of the precursor.
[0099] 2. The first sintered product was crushed and sintered at 460°C together with 0.15 wt.% WO3, 0.05 wt.% TiO2 and 0.15 wt.% Al(OH)3 to obtain the final product; the weight percentages in step 2 are all based on the weight of the first sintered product.
[0100] Comparative Example 2 1. Co-precipitate the precursor Ni 0.6 Co 0.1 Mn 0.3 A mixture of (OH)2, lithium nitrate with a molar ratio of 1.03:1 to the precursor, and dopants 0.22wt.% ZrO2 and 0.12wt.% WO3 is sintered once at a temperature of 900°C to obtain a first sintered product; the weight percentages in step 1 are all based on the weight of the precursor.
[0101] 2. The first sintered product was crushed and sintered at 460°C together with 0.15 wt.% WO3, 0.05 wt.% TiO2 and 0.15 wt.% Al(OH)3 to obtain the final product; the weight percentages in step 2 are all based on the weight of the first sintered product.
[0102] Comparative Example 3 1. Spray pyrolysis precursor Ni 0.6 Co 0.1 Mn 0.3 O, a mixture of lithium nitrate with a molar ratio of 1.03:1 to the precursor and dopants 0.32wt.% ZrO2 and 0.15wt.% MgO is sintered once at a sintering temperature of 900°C to obtain a first sintered product; the weight percentages in step 1 are all based on the weight of the precursor.
[0103] 2. The first sintered product was crushed and sintered at 460°C together with 0.15 wt.% WO3, 0.05 wt.% TiO2 and 0.15 wt.% Al(OH)3 to obtain the final product; the weight percentages in step 2 are all based on the weight of the first sintered product.
[0104] 2. The first sintered product was crushed and sintered at 460°C together with 0.15 wt.% WO3, 0.05 wt.% TiO2 and 0.15 wt.% Al(OH)3 to obtain the final product; the weight percentages in step 2 are all based on the weight of the first sintered product.
[0105] Performance Testing: Test of D50 and Span value of positive electrode material: Mastersizers 3000 were used to characterize the particle size distribution of the materials. The characteristic particle size distribution width of the above materials is expressed as the function Expressed as: ; The above formula represents a typical particle size distribution width function. The larger the Span value, the wider the material particle size distribution.
[0106] The particle size with a number distribution frequency less than or equal to the percentage n% is: .
[0107] Test of the value of the average longest axis D of primary particles The morphology of the material was measured by Hitachi S4800 type Electron microscopy characterization. A Hitachi S4800 high-power electron microscope was used, and the powder samples were directly tested without processing. Photos were taken at 3K magnification. The longest diameter of all particles in the photo was measured, and then the average value was calculated to obtain the average longest axis D of the primary particles of the material. Specifically, the longest sides of all primary particles in the 3000x electron microscope picture were measured using the software "Nano Measurer 1.2" and the average value was calculated to obtain the D value.
[0108] XRD test X'Pert Powder (PANalytical) was used to characterize the crystallographic structure of the material under the following conditions: scanning range: 2θ=10-90°C, scanning time 4.8 min; the obtained (XRD) results were peak-finding and analyzed using professional software to obtain the half-peak widths and peak positions of 003 and 104.
[0109] The half-peak width is converted into the parallel spacing of atoms by the Scherrer formula to obtain the values of d003 and d104. That is:
[0110] where d x is the parallel distance of atoms on a certain surface; is a constant; is the X-ray wavelength; is the half-maximum width (FWHM) of the diffraction peak; is the diffraction angle. Then the value of Dp is obtained by averaging d003 and d104.
[0111] Tap density test The test was carried out using an American Quantachrome tap density tester (model: DAT-4-220).
[0112] Compacted density test The American carver 4350 test was used, and the steps were as follows: weigh 1g of sample, put it into the mold and press it with a pressure of 3T for 30s. After pressing, the height was tested to calculate the compaction.
[0113] Powder resistivity test The powder resistivity is measured by ST2722-SZ powder resistivity tester, and the steps are as follows: 1. Take the powder sample and add it into the feeding chamber until it is full and slightly overflowing, then use a small spoon to slightly compact and flatten it; 2. Turn the hand wheel counterclockwise to press down the upper electrode. Pressurize in stages until the pressure to be measured is reached, and read the pressure and resistivity of the pressed powder on the panel of the test instrument.
[0114] Electron Backscatter Diffraction (EBSD) Test: The cathode material sample was first embedded in a carbon paint (PELCO) graphite block, and then the cross section of the block was polished with an argon ion beam. Electron backscatter diffraction (EBSD) imaging was performed using a JEOL JSM-7000F scanning electron microscope. The step size of the EBSD image was set to 250 nm (each pixel was 250 nm × 250 nm).
[0115] The positive electrode material containing single grains with the same orientation can be tested by electron backscatter diffraction (EBSD). By observing and measuring the colors of different particles, it can be determined whether it contains single grains with the same orientation. Then, by observing and measuring the EBSD or SEM image, the particle size of the selected single grains with the same orientation (i.e., the length of the longest axis of a single grain) can be determined.
[0116] The electrochemical performance of the material was evaluated using a button half-cell. The specific steps are as follows: 1. Ingredients: NCM: SP: 5% PVDF glue = 9.3 g: 0.5 g: 4.0 g, NMP = 9g, stir at high speed to disperse evenly.
[0117] 2. Coating and drying: Evenly coat the slurry on 20μm thick aluminum foil with a 210um coater, set the coating length to the maximum length of the coater, cut the back half of the electrode and put it into a 100℃ forced air drying oven to dry for more than 1.5 hours.
[0118] 3. Rolling, punching and drying: When rolling, adjust the roller machine to 1 roller gap and roll for 3 times; use a 14mm punching machine to punch holes, weigh, and place in a vacuum drying oven for vacuum drying at 85°C for more than 8 hours.
[0119] 4. Assembly of the button (LIR2016): Positive electrode shell - 2 drops of electrolyte - positive electrode sheet (14mm) - 3 drops of electrolyte - 20μm separator - 2 drops of electrolyte - φ16*1.0mm lithium sheet - 150μm nickel foam - negative electrode shell (dried at 50℃). After the battery is assembled, seal it and take it out of the glove box for testing.
[0120] 5. Power-off test After standing for 12 hours, perform the battery test according to the following system: 0.1C charge and 0.1C discharge for 2 weeks (first effect), constant voltage cut-off current 0.005C; 0.5C charge and 0.5C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 1C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 2C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 1C discharge for 50 cycles, constant voltage cut-off current 0.05C.
[0121] Repeat the above steps of button battery assembly, and conduct button battery high temperature cycle retention test. Place the battery in a 45℃ constant temperature box for charge and discharge test. The steps are as follows: After standing for 12 hours, perform the battery test according to the following system: 0.1C charge and 0.1C discharge for 2 weeks (first effect), constant voltage cut-off current 0.005C; 0.5C charge and 0.5C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 1C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 2C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 1C discharge for 50 cycles, constant voltage cut-off current 0.05C.
[0122] Repeat the above steps to perform a low-temperature DCR test, and place the battery in a 25°C constant temperature box for charge and discharge pre-activation: 0.1C charge and 0.1C discharge for 1 week (activation), constant voltage cut-off current 0.005C; 0.1C charge and 0.1C discharge to 3.72V, rest for 6h; 2C discharge for 1 minute, one point every 0.1s; The low-temperature DCR data is finally obtained through the above data processing.
[0123] Table 1 Comparison of performance parameters of positive electrode materials of embodiments and comparative examples
[0124] Table 2 Comparison of positive electrode sheets of the embodiment and the comparative example
[0125] Combination Figures 1 to 4 It can be seen that the particles in the positive electrode materials prepared in Examples 1 to 4 of the present application have good dispersion and no obvious agglomeration. Figure 6 It can be seen that the positive electrode material in Comparative Example 1 is obviously agglomerated and has poor dispersibility.
[0126] Combining the results of Table 1 and Table 2, it can be seen from Example 1 that the positive electrode material of Example 1 has a crystallite coefficient P of 20650, which is within the range of 20000≤P≤100000, indicating that there are more crystallites in the primary particles, and a certain gap between the crystallites can provide a transmission channel for lithium ions, thereby increasing the lithium ion transmission channel in the primary particles, thereby reducing DCR (Direct Current Resistance) and improving the capacity and cycle life of the battery. At the same time, the average longest axis diameter of the positive electrode material is 2.12um, the primary particles of the positive electrode material are larger, and the interplanar spacing d in the 104 crystal plane direction is 0. 104 It is 77.3nm, indicating that there are a large number of microcrystals in the primary particle, which solves the problem of insufficient primary particle growth of traditional single crystal particles; while the material grows into a large-grained single crystal, the number of microcrystals in the particle increases, thereby enhancing the ionic conductivity of the material, which not only solves the problem of large-grained single crystal growth, but also solves the problem of large-grained single crystal with high impedance and low capacity.
[0127] Combining the results of Table 1 and Table 2, it can be seen from Examples 1-10 that the present application forms a precursor of a spinel structure by spray pyrolysis, and then reduces the amount of lithium salt used in the first sintering process to promote the doping of high-valent element X to control the density of the crystal nucleus. At the same time, the temperature of the first heat treatment is relatively low, which can promote the growth of crystallites in the primary particles. The temperature of the second heat treatment is relatively high, which can promote the growth of primary particles, so that the crystallite coefficient P of the primary particles satisfies 20000≤P≤100000, indicating that there are more crystallites in the primary particles, and there are certain gaps between the crystallites to provide a transmission channel for lithium ions, thereby increasing the lithium ion transmission channel in the primary particles, thereby reducing DCR (Direct Current Resistance) and improving the capacity and cycle life of the battery. Moreover, the average length of the longest axis of the positive electrode material is D>2.0μm, d 104 The value of satisfies 20-100nm, indicating that while the primary particles grow into large-grain single crystals, the number of microcrystals in the particles increases, thereby enhancing the ionic conductivity of the material, which not only solves the problem of large-grain single crystal growth, but also solves the problem of large-grain single crystals with high impedance and low capacity.
[0128] From Table 1 and Table 2, it can be seen that the precursor prepared by the co-precipitation process in Comparative Example 1 is not doped with high-valent elements. The average longest axis diameter D of the primary particles and the interplanar spacing in the 104 crystal plane direction are small, and the crystallite coefficient P is less than 20000, indicating that the primary particles are small and have fewer crystallites inside. Its DCR (Direct Current Resistance) is high, and the battery capacity and cycle life are poor.
[0129] From Table 1 and Table 2, it can be seen that the precursor prepared in Comparative Example 2 is prepared by a co-precipitation process and is doped with high-valent elements. The high-valent elements inhibit the growth of primary particles, and the average longest axis diameter D of the primary particles and the interplanar spacing in the 104 crystal plane direction are small. The crystallite coefficient P is less than 20000, indicating that the primary particles are small and have fewer crystallites inside. Its DCR (Direct Current Resistance) is high, and the battery capacity and cycle life are poor.
[0130] From Table 1 and Table 2, it can be seen that Comparative Example 3 uses spray pyrolysis to prepare the precursor, and does not use high-valent elements for doping. In the absence of high-valent elements doping, the average longest axis diameter D of the primary particles obtained in Comparative Example 3 and the interplanar spacing in the 104 crystal plane direction are small, and the crystallite coefficient P is less than 20000, indicating that the primary particles are small and have fewer crystallites inside, and its DCR (Direct Current Resistance) is high, and the battery capacity and cycle life are poor.
[0131] The embodiments of the present application are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and its core idea of the present application. At the same time, changes or deformations made by those skilled in the art based on the ideas of the present application, the specific implementation methods and the scope of application of the present application, all belong to the scope of protection of the present application. In summary, the content of this specification should not be construed as a limitation on the present application.
Claims
1. A positive electrode material, the positive electrode material is a lithium nickel cobalt composite oxide, the positive electrode material comprises a plurality of crystal grains, the crystal grains comprise primary particles, characterized in that: The positive electrode material has a primary particle crystallite coefficient P, , the crystallite coefficient P satisfies 20000≤P≤100000; wherein, d 104 is the interplanar spacing of the 104 crystal plane; D is the length of the average longest axis of the primary particles.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: a) In the XRD spectrum of the positive electrode material, there is a first peak between 17°-20° of 2θ, and the half-peak width of the first peak is 0.08-0.20, and there is a second peak between 42°-45° of 2θ, and the half-peak width of the second peak is 0.10-0.30; b) The positive electrode material has a 003 crystal plane interplanar spacing d 003 , d 003 80-160nm; c) the above 104 20-100nm.
3. The positive electrode material according to claim 1, characterized in that The length average value D of the longest axis of the primary particles, wherein D>2.0 μm.
4. The positive electrode material according to claim 1, characterized in that The grains have the same orientation, and the length of the longest axis of the grains is 1 μm-5 μm.
5. The positive electrode material according to claim 1, characterized in that The positive electrode material has a chemical formula of Li a Ni x M y N z X 1-x-y-z O 2b , wherein 0.98≤a≤1.05, 0.60≤x<1, 0<y≤0.40, 0≤z≤0.003, 0.95≤b≤1.05; M is selected from at least one of Co, Mn, and Al, N is selected from one or more of Ti, Zr, Mg, Sr, Ba, Nb, B, W, and Al, and X is selected from one or more of W, Y, Mn, Os, Sb, and V.
6. The positive electrode material according to claim 5, characterized in that The crystal grain comprises an inner region, the distance between any point in the inner region and the surface of the crystal grain is greater than 500 nm, and at least part of the element X is located in the inner region.
7. The positive electrode material according to any one of claims 1 to 6, wherein the positive electrode material satisfies at least one of the following conditions: a) Powder resistivity of the positive electrode material ; b) The compaction density of the positive electrode material is ≥3.00 g / cc.
8. The positive electrode material according to any one of claims 1 to 6, wherein the positive electrode material satisfies at least one of the following conditions: a) The volume distribution median particle size D50 of the positive electrode material satisfies: 3 um <D50<5um; b) The volume particle size distribution width of the positive electrode material is span, span= , the span value satisfies: 1.0≤Span≤1.
8.
9. The positive electrode material according to claim 1, characterized in that The ratio of the discharge capacity of the positive electrode material at 0.1C to the charge capacity is ≥90.0%, and the ratio of the discharge capacity of the positive electrode material at 0.5C to the discharge capacity at 0.1C is ≥96.5%.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Cobaltosic oxide and preparation method thereof, positive electrode material, lithium ion battery and electric equipment
CN117735620A
Iron phosphate material as well as preparation method and application thereof
CN118545688A
High-nickel-based single-crystal positive electrode precursor, positive electrode material, preparation method of positive electrode material, positive electrode and battery
CN118854459A
Positive-electrode material for lithium secondary-battery, process for producing the same, positive electrode for lithium secondary battery, and lithium secondary battery
US20130029216A1
Cited By
Lithium oxide preparation method, system and equipment
CN120069230A
Low-polarization single-crystal ternary positive electrode material prepared by independent fusion and application thereof
CN120709357A
Positive electrode material and lithium-ion battery
WO2026138634A1